Assessing the Psychological Impact of the Pandemic COVID -19 in Uninfected High-Risk Population - Ahmed,Sami Mustafa Jafar; Awadelgeed,Bashir Ali; Miskeen,Elhadi (Journal of Multidisciplinary Healthcare, 2022)
Sami Mustafa Jafar Ahmed,1 Bashir Ali Awadelgeed,2 Elhadi Miskeen3,4 1Department of Family and Community Medicine,Al Kharj Military Industries Corporation Hospital, Riyadh, Saudi Arabia; 2Chemistry Department, Faculty of Science, Bakht Er-Ruda University, Ed Dueim, Sudan; 3Department of Obstetrics and Gynaecology, College of Medicine, University of Bisha, Bisha, Saudi Arabia; 4Department of Obstetrics and Gynaecology, Faculty of Medicine, University of Gezira, Wad Medani, SudanCorrespondence: Sami Mustafa Jafar Ahmed, Department of Family and Community Medicine,Â Al Kharj Military Industries Corporation Hospital, Riyadh, Saudi Arabia, Tel +966559131609, Email Samimustafa2009@hotmail.comPurpose: To assess the impact of the COVID-19 pandemic on the psyche of uninfected people with chronic diseases in the Elduim community, White Nile State, Sudan, during the COVID -19 pandemic.Methods: We used a generalized anxiety disorder scale (GAD -7) and a patient health questionnaire (PHQ-9) for psychological assessment. The study included two hundred thirty-four participants; all participants with a chronic disease but not infected with COVID -19 were between 24 and 65 years of age. Residents of the study area were randomly selected. Descriptive statistics and a t-test were used for associations with a p-value of 0.05 or less.Results: This study found that anxiety rated by GAD 7 was either mild (18, 7.7%), moderate (98, 41.9%), or severe (41, 17.5%) among participants. PHQ 9-rated depression showed 22 (9.4%) mild depression, most of them in participants aged 36â€“ 44 years. Participants with kidney disease showed major depression 11 (42.31%). Factors that significantly affected anxiety scores were age 24â€“ 35 years (P =0.002), university graduates (P < 0.000), married (P < 0.000), those with diabetes and hypertension (P =0.041), and urban residents (P < 0.023). Those who had secondary education were married and smoked were significantly more likely to have major depression than those with another educational status ...